2004
DOI: 10.1172/jci200419557
|View full text |Cite
|
Sign up to set email alerts
|

Vanin-1–/– mice show decreased NSAID- and Schistosoma-induced intestinal inflammation associated with higher glutathione stores

Abstract: Vanin-1 is a membrane-anchored pantetheinase highly expressed in the gut and liver. It hydrolyzes pantetheine to pantothenic acid (vitamin B5) and the low-molecular-weight thiol cysteamine. The latter is believed to be a key regulating factor of several essential metabolic pathways, acting through sulfhydryl-disulfide exchange reactions between sulfhydryl groups of the enzymes and the oxidized form, cystamine. Its physiological importance remains to be elucidated, however. To explore this point, we developed V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 51 publications
2
51
0
Order By: Relevance
“…The findings that kidney and liver tissues derived from mouse lacking vanin-1 gene were devoid of pantetheinase activity and tissue cysteamine verified the identity of mouse vanin-1 to an active pantetheinase enzyme in mice (Pitari et al, 2000). Studies using vanin-1-deficient mice demonstrated that cysteamine, a metabolite of pantetheinase, has important roles in inflammation (Berruyer et al, 2006), immune function (Martin et al, 2004;Meghari et al, 2007), and regulation of oxidative stress (Berruyer et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…The findings that kidney and liver tissues derived from mouse lacking vanin-1 gene were devoid of pantetheinase activity and tissue cysteamine verified the identity of mouse vanin-1 to an active pantetheinase enzyme in mice (Pitari et al, 2000). Studies using vanin-1-deficient mice demonstrated that cysteamine, a metabolite of pantetheinase, has important roles in inflammation (Berruyer et al, 2006), immune function (Martin et al, 2004;Meghari et al, 2007), and regulation of oxidative stress (Berruyer et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…Vanin 1-deficient mice are not only resistant to gut inflammation but also show increased resistance to stress (Berruyer et al, 2004(Berruyer et al, , 2006Martin et al, 2004;Gensollen et al, 2013). Both vanin 1 and vanin 3 were upregulated (at both the mRNA and the protein levels) by psoriasis-associated proinflammatory cytokines in human keratinocyte cultures (Jansen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Both vanin 1 and vanin 3 were upregulated (at both the mRNA and the protein levels) by psoriasis-associated proinflammatory cytokines in human keratinocyte cultures (Jansen et al, 2009). One way in which vanin 1 promotes this inflammatory reaction and intestinal injury is by decreasing the activity of -glutamylcysteine synthetase and thereby decreasing the stores of reduced glutathione (Berruyer et al, 2004;Martin et al, 2004). Additionally, vanin 1 is strongly induced by fasting: Chen and coworkers have shown that it activates gluconeogenesis and increases glucose output in hepatic cells and that this is mediated through the Akt signalling pathway (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…12 In infectious models, the level of pantetheinase activity (PA) also affects the physiopathological outcome. 10,13 Splenic PA has been shown to contribute to malaria resistance by limiting the level of parasitemia in a Plasmodium chabaudi model of infection. 14 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 model, cysteamine specifically affected parasite development.…”
mentioning
confidence: 99%